The Factors Affecting Students’ English Speaking Ability at Politeknik LP3i Medan - Ramadani, Ramadani; Hamdani, Sukri (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2021)
This study deals with the factors affecting students’ English speaking ability at Politeknik LP3I Medan. It uses qualitative research design with a single case study to gain an understanding on this study. It is conducted descriptively. This study aims to know the factors affecting students’ English speaking ability at Politeknik LP3I Medan. The subjects were 20 students (males and females) of Politeknik LP3I Medan. The instruments in this study were observation and interview. The theories of Brown (1994: 4) are divided some factors which affect speaking, they are Chronological Age, Grammar, Vocabulary, Fluency, and Comprehension. There are three factors affecting students’ English speaking ability at Politeknik LP3I Medan. They are fluency, vocabulary and English environment and an additional factor that found by researcher as a new insight in this research is English environment. Analysis of data clearly indicates that the students are using English at campus every day.This study deals with the factors affecting students’ English speaking ability at Politeknik LP3I Medan. It uses qualitative research design with a single case study to gain an understanding on this study. It is conducted descriptively. This study aims to know the factors affecting students’ English speaking ability at Politeknik LP3I Medan. The subjects were 20 students (males and females) of Politeknik LP3I Medan. The instruments in this study were observation and interview. The theories of Brown (1994: 4) are divided some factors which affect speaking, they are Chronological Age, Grammar, Vocabulary, Fluency, and Comprehension. There are three factors affecting students’ English speaking ability at Politeknik LP3I Medan. They are fluency, vocabulary and English environment and an additional factor that found by researcher as a new insight in this research is English environment. Analysis of data clearly indicates that the students are using English at campus every day.